Islam and the secular state negotiating the future of Shariʻa - Naim, Abd Allah Aḥmad, 1946- (Harvard University Press, 2008)
What should be the place of Shari 'a - Islamic religious law - in predominantly Muslim societies of the world? This book envisions a positive and sustainable role for Shari 'a, based on a profound rethinking of the relationship between religion and the secular state in various societies.